Generation and characterization of TAL effector nucleases with novel catalytic domains - Bietz, Fabian; Justus Liebig University Giessen (My University, 2015)
Site-specific nucleases (SSNs) are molecular tools to introduce DNA double-strand breaks (DSBs) at definite genomic loci. DSBs can be exploited to knock-out, delete, repair or insert genes of interest. Construction of ssns was simplified tremendously with the discovery of transcription activator-like effector (TALE) proteins. The novel TALE nucleases (TALENs) consist of a TALE-derived DNA binding domain, guiding the construct to its target site, and a nuclease domain, which is cleaving the DNA. The standard nuclease domain is the catalytic domain of type IIS restriction endonuclease FokI, which was adopted from the older zinc-finger-nuclease architecture. FokI requires dimerization for the creation of a DSB, making two TALENs necessary. Aim of this work is the replacement of this catalytic domain to generate monomeric TALENs, that simplify production and transfection. To cover nuclease domains with varying degrees of specificity, three groups were chosen: promiscuous H-N-H and DRGH nucleases (I), the more specific I-TevI catalytic domain (II) and variants of the highly-specific homing endonuclease I-CreI (III). The selected domains were adapted to the fusion scaffold via rational design strategies and tested in vitro and in vivo in several model organisms. Special properties of these domains made the generation of novel, monomeric TALENs possible. Colicin E7, Nuclease A and Endonuclease A (I) were used to create switchable TALENs and I-CreI (III) fusion yielded a highly specific construct. Investigation of the influence of the fusion terminus allowed the construction of scaffolds with multiple nuclease domains via I-TevI (II) and FokI.

Hoch-spezifische Nukleasen (SSNs) sind molekulare Werkzeuge um DNA-Doppelstrangbrüche (DSBs) an definierten Stellen im Genom zu erzeugen. Diese dsbs können für Gen-Knockout, -Deletion, -Reparatur oder -Insertion genutzt werden. Die Herstellung der SSNs wurde durch die Entdeckung der Transcription Activator-Like Effector-(TALE)-Proteine enorm vereinfacht. Die neuen TALE-Nukleasen (TALEN) bestehen aus einer TALE-basierten DNA-Bindedomäne, die das Konstrukt zu seiner Zielsequenz führt, und einer Nukleasedomäne, welche die DNA schneidet. Die gängigste Nukleasedomäne ist die katalytische Domäne der Typ IIS Restriktionsendonuklease FokI, die aus der älteren Zinkfingernukleasen-Architektur übernommen wurde. Da FokI eine Dimerisierung zur DSB-Erzeugung erfordert, werden zwei TALENs benötigt. Ziel dieser Arbeit ist der Austausch dieser katalytischen Domäne um monomere talen, die Herstellung und Transfektion vereinfachen, anzufertigen. Um Nukleasedomänen mit verschiedenem Grad an Spezifität abzudecken, wurden drei Gruppen ausgewählt: unspezifische H-N-H und DRGH Nukleasen (I), die spezifische, katalytische Domäne von I-TevI (II) und Varianten der hoch-spezifischen Homingendonuklease I-CreI (III). Die gewählten Domänen wurden durch rationales Design für die Fusion adaptiert und in vitro sowie in vivo in verschiedenen Modelorganismen getestet. Die besonderen Eigenschaften der jeweiligen Domänen machte die Entwicklung neuartiger, monomerer TALEN möglich. Colicin E7, Nuklease A und Endonuklease A (I) wurden verwendet um regulierbare TALEN zu erzeugen und aus der Fusion mit I-CreI (III) entstand eine hoch-spezifischen Nuklease. Untersuchungen über den Einfluss des Fusionsterminus erlaubte die Herstellung von Gerüsten mit multiplen Nukleasedomänen mittels I-TevI (II) und FokI.
Keywords: TALEN; Nukleasen; Protein-Engineering; Genome-Editing; TALEN; nucleases; protein engineering; genome editing; ddc:570